PERAN DIGITALISASI PEMASARAN DALAM MENDORONG PERTUMBUHAN PENJUALAN : STUDI KASUS TOKO ROSE COLLECTION PALU - Selfina Lahabu; Erwinsyah; Phatra Anggana Djuri; Femilia Zahra (Jurnal Nusa Manajemen, 2025)
This study aims to examine how digital marketing through social media is utilized to increase sales and customer loyalty at Rose Collection Palu, a local fashion SME. The research uses a descriptive qualitative method with data collected through in-depth interviews, observation, and documentation. The findings show that TikTok, Instagram, and Facebook are actively used as the main platforms for promotion, communication, and customer engagement. Visual content strategies that align with current trends are proven to boost audience interaction and build brand image. Digitalization significantly contributes to sales growth, with online sales accounting for 60% and a notable increase in new customers. However, challenges such as algorithm fluctuations and limited content production tools remain. This study contributes as a reference for SMEs to develop adaptive digital strategies and provides input for policymakers in supporting digital transformation among micro-businesses.